Modern Education: The Advantage and Effectiveness of Distance Learning - Navruzova, Elena Pavlovna; Isroilova, Guzal Ravshanovna; Khasanov, E. R. (Research Parks Publishers, 2022)
This article discusses distance learning and its advantages. The concept of